Establishing PCR Testing in Nepal for Covid-19: Challenges and Opportunities - Khadka, R. B.; Gyawali, R. (Kathmandu University Medical Journal, 2020)
Polymerase chain reaction (PCR) invented by Kary Mullis (1983), has become the centrepiece of molecular detection of various infectious diseases including coronavirus disease 2019 (COVID-19). Many developing countries like Nepal faces various challenges and grab many future opportunities during and after establishment of molecular PCR laboratories throughout the country. This viewpoint describes the involvement of laboratory employees, development and adoption of new protocols or framework, deliberate partnership with national and international community is very efficient for the establishment of PCR laboratories. Beside this, continued alliance and nation leadership is crucial to generate a unified and sustainable PCR laboratory network in the country like Nepal. In future the established PCR laboratories can be utilized for the diagnosis of others pandemic diseases and can be used for multipurpose like in verification of infectious diseases; Oncology; Blood test; Genetic testing.